Frekuensi Konsumsi Junk Food, Status Gizi dan Usia Menarche pada Siswi SMP Dharma Praja Kabupaten Badung Provinsi Bali - Ni Nyoman Purwita Sari; Desak Putu Sukraniti; I Made Rodja Suantara (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Menarche is the first menstruation that occurs in women. According to Riskesdas, the prevalence of menarche 12 years is 5.2%. The purpose of this research is to know the correlation trend between frequency of junk food consumption with nutritional status, nutritional status with menarche age and frequency of junk food consumption with menarche age. This type of research is an observational study with cross-sectional design. The sampling technique of this research is by proportional simple random sampling method. The sample of this study amounted to 76. Frequency of consumption was collected with FFQ media, nutritional status calculated by z-Score and age of menarche collected by questionnaire. The results were analyzed by univariate and bivariate tables. Result of frequency analysis of junk food consumption with nutritional status get result that there is tendency of correlation between frequency of consumption of junk food with nutritional status. The result of nutritional status analysis with age of menarche has resulted that there is no correlation between nutritional status with age of menarche. The result of frequency analysis of junk food consumption with age of menarche get result that there is tendency of correlation between frequency of consumption of junk food with age of menarche .As a conclusion from this research that there is tendency of correlation between frequency of consumption of junk food with nutritional status and between frequency of consumption of junk food with age menarche but there is no trend of nutritional status correlation with age of menarche.Keywords: junk food, nutritional status, menarche, a female student